Adsorpsi Air dari Campuran Uap Etanol-Air dengan Zeolit Sintetis 4A dalam Packed Bed dalam Rangka Produksi Fuel Grade Ethanol - Handrian Handrian; Wahyudi Budi Sediawan; Aswati Mindaryani (Jurnal Rekayasa Proses, 2017)
Ethanol can be used as fuel if it has a purity of 99.5%, while ethanol distillation will stop at its azeotrop point, ie at 95.6%. Adsorption of molecular sieve is one of the methods to obtain ethanol with level above the azeotropic point. Adsorbent that serves as molecular sieve is synthetic zeolite 4A. The adsorbent has a pore diameter of 3.9 Ǻ, then water and ethanol each has a molecular diameter of 2.75 Ǻ and 4.4 Ǻ. Hence the adsorbent is selective against the ethanol-water mixture. The purpose of this research is to obtain ethanol above its azeotropic point and to study the relationship between the influence of flow rate (Vz) and temperature (T) to changes in the number of mass transfer coefficient (kc), radial diffusivity (Der) and henry constants (H') which can be used as parameters in the design of adsorption tools on a commercial scale.This experiment was conducting by weighing zeolite 4A as much as 100 grams, then compiled and measured the height on packed bed column adsorbent. The heating regulator is switched on and set to a constant temperature of 80, 85, 90, 95 and 100 0C. Ethanol 95.61% with 250 ml volume is put into three-neck flask, then heat to evaporate. Turn on the cooling back and adjust the amount of formed vapor rate by adjusting the faucet opening and the degree of voltage in the heating mantle. The magnitude of the vapor flow rate is set at 2, 4 and 6 liters / minute. The products is accomodated and samples were taken every minute to analyze the ethanol content.This adsorption process gives the highest yield of ethanol with 99.40% content. The steam flow rate of 2 lpm and the temperature of 800C is the optimum combination in this research because much of the water vapor adsorbed on the 4A zeolite grain is 7.93 grams. The numerical calculation provides the result that the value of Der in this experiment is 1.59.10-3 cm2 / men, and the relation of kc are the function of reynolds and H'  the function of temperature are as follows: kc = 7,95.10^-3.(Re)^0,1639 and H' = 4,47.10^-3.exp(2565,26/T) ABSTRAKEtanol dapat digunakan sebagai bahan bakar jika memiliki kemurnian 99,5%, sedangkan dislitasi etanol akan terhenti pada titik azeotropnya, yaitu pada 95,6%. Adsorpsi molecular sieve adalah salah satu metode untuk memperoleh etanol dengan kadar diatas titik azeotrop. Adsorbent yang berfungsi sebagai molecular sieve adalah zeolit sintetis 4A. Adsorbent ini memiliki diameter pori sebesar 3,9 Ǻ, lalu air dan etanol masing-masing memiliki diameter molekul 2,75 Ǻ dan 4,4 Ǻ. Maka dari itu adsorbent bersifat selektif terhadap campuran etanol-air. Penelitian ini bertujuan untuk memperoleh etanol diatas titik azeotropnya serta mempelajari hubungan pengaruh laju alir (vz) dan suhu (T) terhadap perubahan harga koefisien transfer massa (kc), difusivitas radial (Der) dan konstanta henry (H’) yang bisa digunakan sebagai parameter dalam perancangan alat adsorpsi pada skala komersial. Percobaan ini dilakukan dengan cara menimbang zeolit 4A sebanyak 100 gram, lalu disusun  dan diukur tingginya pada packed bed columnadsorbent. Regulator pemanas dinyalakan dan diatur suhunya sampai konstan pada 80, 85, 90, 95 dan 1000C. Etanol 95,61% dengan volum 250 ml dimasukkan ke labu leher tiga, lalu dipanaskan sampai menguap. Pendingin balik dinyalakan dan diatur besarnya laju uap yang terbentuk dengan mengatur bukaan kran dan derajat voltase pada heating mantle. Besarnya laju aliran uap diatur pada 2, 4 dan 6 liter/menit. Produk ditampung dan diambil tiap menit sebagai sampel untuk dianalisis kadar etanolnya. Proses adsorpsi ini memberikan hasil tertinggi berupa etanol dengan kadar 99,40%. Laju alir uap 2 lpm dan suhu 800C adalah kombinasi yang optimal dalam penelitian ini karena banyak uap air yang teradsorpsi pada butir zeolit 4A yaitu 7,93 gram. Perhitungan secara numeris memberikan hasil bahwa nilai Der pada percobaan ini adalah 1,59.10-3 cm2/men, serta hubungan kc fungsi reynolds dan H’ fungsi suhu berturut-turut adalah sebagai berikut:kc=7,95.10-3..vz.D0,1639dan H'=4,47.10-3.e2565,26T